Oral discomfort and health behavior of patients with typical vs. atypical antipsychotic drugs - Meurman, Jukka H.; Murtomaa, Heikki (Frontiers in Psychiatry, 2024)
Introduction: Psychiatric patients suffer from oral diseases and side effects of antipsychotic medication. In particular, the typical antipsychotic drugs may cause severe hyposalivation with subsequent oral symptoms. We therefore aimed to compare oral health behavior and oral side effects of in-hospital patients taking typical vs. atypical antipsychotic drugs with the hypothesis that the former drugs cause more oral pain than the newer drugs.Methods: This cross-sectional questionnaire and interview study investigated subjective oral symptoms and their health behavior in 170 hospitalized psychiatric patients, comparing those taking typical vs. atypical antipsychotic drugs. Cross-tabulations and chi-square tests were used for analyses.Results: Persistent oral pain lasting throughout the day was reported by 46% in the typical, and 5% in the atypical antipsychotic group patients, respectively. In both groups, the pain was mainly in the tongue and buccal mucosa and was described as a burning sensation. A significantly higher prevalence of xerostomia was reported in the typical antipsychotic medication group (66%) compared with the atypical antipsychotic medication group (53%, p<0.01). Self-assessed dental health was assessed as poor by two-thirds of the patients of whom 69% reported toothbrushing once daily. Approximately half of them reported having had a visit to a dentist within the previous year. Of the women 28%, and of the men 17%, respectively, had received professional consultations for oral symptoms.The current results on psychiatrically hospitalized patients emphasize the need for awareness of oral discomfort and its subsequent effects on the quality of life in this challenging patient group. Focus should also be placed on a wide range of support encouraging the patients to maintain good daily oral hygiene and seek professional dental help when needed.